PENGEMBANGAN SOAL CERITA SISTEM PERSAMAAN LINEAR MENGGUNAKAN ANIMASI KOMIK KELAS X SEKOLAH MENENGAH ATAS (SMA) - Fitriani, Henny (Mathematics Education Journal, 2014)
This study is a development research which aims to: (1) generate story problems by using comic animation are valid and practical, (2) know the potential effects story problems by using comic animation to know the problem solving ability in class X Kusuma Bangsa Senior High School. The subject of this research is 27 students of the X.6 grade student of Kusuma Bangsa Senior High School. The data collecting technique used is walk through to know the validity of the the problem of its content, construction, and language; documentation used to know the practicality of the problem; and test used to know the potential effect of story problem of Linear Equation System by using comic animation to know the problem solving ability of the 10th grade student of Senior High School. The result concludes that (1) this research is resulted in a product story problem of Linear Equation System by using comic animation as much as 10 questions to know the valid and practical problem solving ability of the 10th grade student. The validity is indicated from the result of the validity assessments and problem analysis. The practicality is indicated from the small group and field test try out result which most of the student can understand the problem well. (2) Prototype developed has the potential effect to student problem-solving abilities. This is illustrated from the student's ability to understand the problem and then make a mathematical model of the problem, choosing an appropriate strategy to solve the problem, and explain the results obtained in accordance with the problem. DOI: https://doi.org/10.22342/jpm.8.2.1865.33-43